The impact of desilication products on the flocculation and sedimentation properties of bauxite residue - Senaputra, Alexander (Curtin University, 2014)
In the Bayer processing of bauxite, dissolved silica re-precipitates as aluminosilicates or desilication products (DSPs) that adversely affect residue separation by flocculation and thickening prior to product precipitation. DSP was shown to form at the surface of hematite, impacting upon the extent, efficiency and mechanism of aggregation with a number of different polymer reagents. Real-time measurement of aggregate properties provided new insights on fines capture. The practical implications for full-scale feedwell flocculation were explored.